Cornici pedagogiche per la formazione docente : Il ruolo dell'insegnante di sostegno nella co-costruzione di contesti inclusivi - Amatori, Gianluca (Milan FrancoAngeli, 2019)
The volume reviews the fundamental issues of teacher training, especially about the support teacher, to re-establish new coordinates for the co-construction of inclusive class contexts.
Italian
Keywords: Education; teacher training; support teacher; inclusion; school; International Classification of Functioning, Disability and Health; ICF